eLearning for edLeaders at Emporia State University - John Morton; Daniel Stiffler; Nancy Albrecht; Timothy Marshall (The Advocate, 2018)
The building level leadership practicum at Emporia State University in Emporia, KS, has moved from a face-to-face experience to a totally online experience. Students participate in 56 total learning activities which are reported online for the two semester course. The program provides flexibility to students and still allows quality interaction via structured discussions. In addition, students select a practicum research project which allows them to gain hands on experiences by following the project from start to completion. The shift in program has garnered positive student response and support. This program utilizes elearning to prepare graduate building level leadership students for a 21st century leadership role in schools (SERC, 2017).